Sistema de comunicação virtual da Cooperativa dos cafeicultores de Campos Gerais e Campo do Meio MG - BELO, Juliano Aparecido (2018)
Brazil stands out in the world scenario as a major exporter of commodities, being a reference mainly in the export of coffee. To great extent this scenario can only be built with the support of cooperatives that act as development promoters in the regions in which they are located. However, most of them are small farmers who, for the most part, lack essential information for the development of their properties. Such lack is due to the difficulty of access to this information, which is often not easily accessible in the cooperative institution itself. In this scenario, information technology has contributed to the development of this sector, mainly with the development of virtual systems, which can be accessed via the internet. Therefore, the objective of this work was the development of a virtual platform, linked to an intranet system that allows the Cooperatives of the Cooperatives of the Coffee Growers of Campos Gerais and Campo do Meio (COOPERCAM) to access, in a quick and easy way via desktop or mobile essential information for the development of their jobs like weather forecast, commodity quotes and dollar. At the same time, the cooperative can feed this system with information that the cooperative only has access in person. It is emphasized that the initial screen of the system where the most searched information is available has mobile technology, adjusting to the various devices. The system was developed based on interviews with cooperative members of the COOPERCAM cooperative who verified the importance of having an online system that provides information that is used daily by them. Its access can be realized through the link http://coopercam.redeinterna.com.br.